Sodium-ion battery and preparation method of modified positive active material of sodium-ion battery
By performing positive pressure calcination of NaXTMO2 layered oxide and modifier MaNbOcYd on the sodium ion battery layered oxide positive electrode material, the problem that the material is difficult to take into account both high voltage, fast charge and low temperature performance under high charging voltage, and excellent battery performance is achieved.
Patent Information
- Application Number
- CN202510057632.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-14
AI Technical Summary
It is difficult for existing sodium ion battery layered oxide positive electrode materials to take into account high voltage, fast charging and low temperature performance under high charging voltage.
The positive pressure calcination treatment was performed using NaXTMO2 layered oxide and the modifier MaNbOcYd to achieve low impedance gradient doping and coating of the material through an inline from the outside to the inside.
Improves the high voltage, fast charging and low temperature performance of the material, achieving high capacity, high magnification, long cycles and excellent fast charging and low temperature performance at high voltages.
Smart Images

Figure CN119864398A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium secondary batteries, and in particular to the field of positive electrode materials. Background Art
[0002] Layered oxide cathode materials for sodium ion batteries have the advantages of high energy density, high operating voltage, and simple preparation process. They are one of the most widely used and promising key materials in the field of sodium ion batteries. At present, with the development of sodium ion batteries, the requirements for battery energy density are higher. For layered oxides, although increasing the charge cutoff voltage of the material can increase its specific capacity, the cycle and rate performance of the layered oxide will decrease. Among them, the irreversible phase change under high charge cutoff voltage and the thickening of the electrolyte cathode interface film caused by side reactions at the interface between the material and the electrolyte are the main reasons affecting the material cycle and rate performance. Therefore, it is necessary to coat and gradient dope the layered oxide cathode material.
[0003] Surface modification, such as coating the surface of layered oxide positive electrode materials with metal oxides ZrO2, metal fluorides AlF3, metal phosphates NaPO4, etc., can prevent the dissolution of transition metals, reduce adverse side reactions at the interface between the electrolyte and the positive electrode, and improve the cycle stability of the material.
[0004] At present, the positive electrode surface coating materials used for industrial production at home and abroad are mainly metal oxides. The surface coating purpose is achieved by mixed sintering of the coating material and the positive electrode active material. During the coating, the metal oxide can be gradiently doped into the surface of the base material to improve the irreversible phase change and further improve the high-voltage stability of the material.
[0005] For example, Chinese patent document with publication number CN114613981A discloses a zinc-doped zinc oxide-coated manganese-based layered oxide material and its preparation method and application, which specifically records a scheme of mixing a sodium source, a nickel source, a copper source, a zinc source and a manganese source in a certain stoichiometric ratio by ball milling and then calcining at a high temperature. A Chinese patent document with publication number CN116314640A discloses a layered oxide positive electrode material for a sodium ion battery, specifically disclosing that a nickel source, a sodium source, a manganese source, an iron source, a Me source, an auxiliary agent, and a dopant are uniformly mixed in proportion to obtain a mixture, the mixture is subjected to a first sintering in an air or oxygen atmosphere, and then the temperature is raised to react for a period of time, the temperature is raised again, and then the sintering is continued. After the sintering is completed, the temperature is lowered to the furnace discharge temperature, and finally the furnace is discharged, crushed, and sieved to obtain a first sintering product; the first sintering product is then mixed with a surface modifier, and after the mixture is uniformly mixed, the temperature is raised to the reaction temperature in an air or oxygen atmosphere, and a second sintering is performed. After the second sintering is completed, the temperature is lowered to the furnace discharge temperature, and the furnace is discharged, crushed, and sieved to obtain a second sintering product; and then the coating agent is uniformly mixed, and the mixture is subjected to a third sintering in an air or oxygen atmosphere, and the third sintering product is sieved to obtain an O3 or P2 type layered oxide positive electrode material.
[0006] In summary, although the existing coating method can improve the high voltage performance to a certain extent, there is an inevitable problem of reduced material capacity and conductivity, making it difficult to take into account high voltage, high rate, fast charging and low temperature performance. Summary of the invention
[0007] In view of the problem that existing positive electrode active materials are difficult to achieve high voltage, fast charging and low temperature performance, the first purpose of the present invention is to provide a method for preparing a modified positive electrode active material, aiming to provide a positive electrode active material for a sodium ion battery that has excellent fast charging and fast charging performance.
[0008] The second object of the present invention is to provide a modified positive electrode active material obtained by the preparation method and its application in sodium ion batteries.
[0009] The third object of the present invention is to provide a sodium ion battery comprising the modified positive electrode active material, and a positive electrode and a positive electrode material thereof.
[0010] The existing coating technology can improve its voltage to a certain extent, but it is easy to lose its fast charging, capacity and other performances, and it is difficult to take into account the high voltage, fast charging and low temperature performances. In view of this problem, the present invention has conducted in-depth research and provided the following improvement scheme:
[0011] A method for preparing a modified positive electrode active material for a sodium ion battery, comprising: X TMO2 layered oxide and modifier are mixed and calcined under positive pressure to obtain;
[0012] Na XIn the TMO2 layered oxide, the TM is one or more of Ni, Fe, Mn, Cu, Ca, Mg, Ti, Al, Zn, Zr, Sn, Sb, and W; the x is 0.5 to 1;
[0013] The modifier is M a N b O c Y d ; the M is at least one of Sn, In, and Cd; the N is at least one of Ga, Sb, Ba, Al, Ti, Zr, La, Ce, Mo, W, Au, Sr, Hf, and Ta; the Y is at least one of F, Cl, Br, and I; the 0 < a ≤ 1; the b is 0 to 0.5; the d is 0 to 0.5; the c is 2 to 0.5d.
[0014] The present invention innovatively uses M a N b O c Y d as an external modifier to perform positive-pressure thermal modification on the Na X TMO2 layered oxide, so that low-impedance gradient doping and coating of the material can be achieved based on the inlay method from outside to inside, and then the high-voltage, fast-charging, and low-temperature performance of the prepared material can be improved.
[0015] In the present invention, the Na X TMO2 layered oxide can be any active material that needs to be modified and is applicable in the field of sodium batteries, and it can be obtained based on existing principles and methods. For example, it can be obtained by sintering a Na source and a TM source.
[0016] In the present invention, the Na source includes at least one of sodium carbonate, sodium sulfate, sodium nitrate, sodium phosphate, sodium chloride, and sodium fluoride.
[0017] In the present invention, the TM source is at least one of a carbonate, hydroxide, organic acid salt, and oxide of the TM element;
[0018] In the present invention, the TM includes at least one of Ni, Fe, and Mn, and also selectively includes one or more of Cu, Ca, Mg, Ti, Al, Zn, Zr, Sn, Sb, and W.
[0019] In the present invention, the molar ratio of Na / TM in the Na source and the TM source is 0.5 - 1.07; further, it can be 1 to 1.05.
[0020] In the present invention, the sintering temperature is 800 to 1500 °C, and further, it can be 1000 to 1400 °C.
[0021] In the present invention, the sintering time is 10 to 15 hours.
[0022] In the present invention, the type of modifier and its embedded thermal modification method from outside to inside are the key to improving the high voltage, fast charging and low temperature performance of the material by coordinating solid gradient infiltration and uniform surface coating, and reducing hierarchical interface impedance, thereby optimizing the ion and electron conduction network and efficiency.
[0023] As an optional solution, the modifier is SnO2, In2O3, CdO, SnO 2-0.5d F d 、InO 2-0.5d F d , CdO 2- 0.5d Br d Sn a Sb b O2、In a Sn b O2、In a Cd b O2、Sn a Sr b O2、In a Ga b O2、Sn a La b Ba c O2、Sn a Ce b O2、In a Ce b O2、In a Sn b O 2-0.5d F d Sn a Sb b O 2-0.5d F d At least one of .
[0024] Furthermore, in the modifier, b and c are not simultaneously 0. In the present invention, when b and c are not simultaneously 0, the fast charging and low temperature performance of the prepared material can be further optimized based on the hybridization of cations and / or anions in the modifier.
[0025] Furthermore, the modifier is SnO 2-0.5d F d 、In a Sn b O 2-0.5d F dAt least one of d is 0.1 to 0.6, and further 0.3 to 0.5. Studies have shown that the preferred modifier combined with the positive pressure calcination process of the present invention can further optimize the fast charging and low temperature performance of the prepared material.
[0026] In the present invention, the M a N b O c Y d Existing commercial products can be selected, or they can be prepared based on conventional solid phase synthesis methods. For example, when the M a N b O c Y d When b and / or d is not 0, it can be obtained by sintering source materials containing the elements; wherein the calcination temperature is 800-1500°C (further 850-950°C); and the calcination time is preferably 10-15h.
[0027] In the present invention, based on the molar mass of the transition metal, the modifier is Na X 1-5 mol% of TMO2 layered oxide and modifier mixture.
[0028] In the present invention, the calcination temperature is 500-900°C (further 650-850°C), and the calcination time is preferably 2-10h (further 6-8h);
[0029] Preferably, the atmosphere during the calcination stage is an oxygen-containing atmosphere;
[0030] Preferably, the pressure in the calcination stage is +20 to +100 Pa.
[0031] The invention also provides a modified positive electrode active material prepared by the preparation method.
[0032] The preparation method described in the present invention can give the prepared material a good interface structural relationship, and the material prepared by the preparation method can unexpectedly take into account the advantages of excellent high voltage, fast charging and low temperature performance.
[0033] The present invention also provides an application of the modified positive electrode active material prepared by the preparation method, which is used as a positive electrode active material to prepare a sodium ion battery.
[0034] The present invention can use the modified positive electrode active material as a positive electrode active material based on conventional principles and means to prepare a sodium ion battery and its positive electrode and positive electrode material.
[0035] For example, in the present invention, the modified positive electrode active material can be combined with a binder and a conductive agent to obtain a positive electrode material, and the positive electrode material can be further coated on a current collector to form a positive electrode. The positive electrode can be further combined with a barrier layer and a negative electrode to obtain a battery.
[0036] The present invention also provides a positive electrode material for a sodium ion battery, which comprises the modified positive electrode active material of the present invention.
[0037] The present invention also provides a positive electrode of a sodium ion battery, which comprises the positive electrode material of the present invention.
[0038] The present invention also provides a sodium ion battery, which comprises the positive electrode described in the present invention.
[0039] The sodium ion battery and the positive electrode and positive electrode material thereof described in the present invention, except for the modified positive electrode active material described in the present invention, other ingredients and components can be conventional.
[0040] Beneficial Effects
[0041] The present invention aims at the problem that the capacity and rate performance of sodium ion battery layered oxide positive electrode materials coated and modified by conventional oxides under high charging cut-off voltage are not ideal, and the modification method is difficult to take into account the performances such as high voltage and fast charging. The layered oxide positive electrode materials are coated with conductive oxides and modified by gradient doping, so as to improve the volume strain and interface problems of the layered oxide positive electrode materials under high charging cut-off voltage while maintaining the original rate performance of the materials.
[0042] It is further preferred that the modifier can improve the electronic (ionic) conductivity of the coating layer while ensuring its high chemical stability, construct a high conductivity (surface) interface, and improve the rate performance of the layered oxide positive electrode material, so that the prepared layered oxide positive electrode material has high capacity, high rate, long cycle, excellent fast charging and low temperature performance under high voltage. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figures 1 to 4 The scanning electron microscope images of Example 1, Comparative Example 1, Comparative Example 4 and Comparative Example 5 are shown; DETAILED DESCRIPTION
[0044] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0045] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0046] The first aspect of the present invention provides a method for preparing a layered oxide positive electrode material, comprising the following steps:
[0047] Step 1: Preparation of layered oxide Na X TMO2 cathode material:
[0048] Take transition metal oxides and Na2CO3 and mix them and then calcine them to obtain Na X TMO2 layered oxide. Wherein, the transition metal oxide and Na2CO3 can be mixed according to the conventional ratio in the art. According to an embodiment of the present invention, the transition metal oxide and Na2CO3 are mixed according to a sodium to transition metal molar ratio of 0.5-1.07, wherein the mixing parameters are not particularly limited, and the mixing is uniform and free of white spots. According to an embodiment of the present invention, the mixing speed is 1500rpm to 2500rpm, and the mixing time is 5 to 15min;
[0049] Furthermore, the transition metal oxide in the present invention is one or more of NiO, Fe2O3, MnO, CuO, MgO, SnO2, Sb2O5, WO3, TiO2, ZnO, CaO, Al2O3, and ZrO2. According to an embodiment of the present invention, based on the molar mass of the transition metal in the precursor, the content of NiO is 5%-40%, the content of Fe2O3 is 10%-40%, the content of MnO2 is 10%-50%, and the content of CuO is
[0050] 1%-10%, SnO2 content is 0.5%-5%, Sb2O5 content is 0.5%-7%, MgO content is
[0051] 0.5%-7%, the content of Al2O3 is 0.3%-3%, the content of TiO2 is 1%-40%, the content of ZnO is 1%-10%, the content of CaO is 1%-5%, the content of ZrO2 is 1%-3%, and the content of WO3 is 1%-5%;
[0052] Furthermore, in the preparation of the layered oxide, gradient sintering is used for sintering, and the gradient sintering process is specifically pre-sintering at 400-500° C. for 6-8 hours, and then heating to 800-1200° C. for 10-15 hours.
[0053] Step 2: Preparation of conductive oxide (modifier):
[0054] The conductive oxide described in the present invention is an anion-cation doped modified conductive oxide, mainly SnO2, In2O3, CdO, SnO 2-0.5d F d 、InO2-0.5d F d , CdO 2-0.5d Br d Sn a Sb b O2、In a Sn b O2、In a Cd b O2、Sn a Sr b O2、In a Ga b O2、Sn a La b Ba c O2、Sn a Ce b O2、In a Ce b O2、In a Sn b O 2-0.5d F d Sn a Sb b O 2-0.5d F d At least one of .
[0055] Further, according to an embodiment of the present invention, the conductive oxide is prepared by a solid phase sintering method known in the art, and the specific steps are as follows:
[0056] The conductive oxide is obtained by mixing source materials containing elements and then sintering; there is no particular limitation on the mixing parameters, as long as the mixing is uniform and there is no white spot. According to an embodiment of the present invention, the mixing speed is 1500rpm to 2500rpm, and the mixing time is 5 to 15min; secondly, the sintering temperature is 800 to 1500°C; and the time is preferably 10 to 15h.
[0057] Step 3: High voltage and high rate layered oxide cathode materials
[0058] Layered oxide Na X The TMO2 positive electrode material and the modifier are mixed evenly, and then the mixture is sintered at 500-900°C for 2-10 hours in a box furnace with an oxygen-containing atmosphere at a pressure of +20-100 Pa. X The molar mass ratio of the transition metal of TMO2 to the conductive oxide modifier is 99:1 to 95:5; the mixing equipment is a vertical mixer, the mixer speed is 1000rpm to 2000rpm, and the mixing time is 5 to 15min.
[0059] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial sources.
[0060] Example 1
[0061] Step 1: Preparation of layered oxide cathode materials
[0062] Take transition metal oxides and Na2CO3 according to the sodium / transition metal molar ratio of 1.05:1;
[0063] The transition metal oxides include Ni, Fe, Mn, Cu, Sn, Sb, Mg, Al, Ti, Zn, Ca, Zr, and W in a molar ratio of 0.3:0.3:0.3:0.03:0.005:0.005:0.01:0.005:0.01:0.005:0.005:0.005:0.005:0.005 of NiO, Fe2O3, MnO2, CuO, SnO2, Sb2O3, MgO, Al2O3, TiO2, ZnO, CaO, ZrO2, and WO3.
[0064] The prepared oxide precursor and Na2CO3 are added to the high-speed mixer in sequence at a mixing speed of 2000 rpm for 10 min. The mixture is evenly mixed without white spots. The mixture is pre-sintered at 500°C for 8 h in an air box furnace, then heated to 1200°C and calcined for 12 h. The mixture is cooled to room temperature with the furnace, and layered oxides are obtained after roller crushing and air flow pulverization.
[0065] Step 2: SnO 1.8 F 0.4 Preparation of Conductive Oxide (Modifier) Powder
[0066] SnO2 and NH4F powders with a molar ratio of F:Sn of 4:10 were added into a vertical mixer and mixed evenly. The mixer speed was 2000 rpm and the mixing time was 10 min. Then the mixture was sintered at 900 °C for 12 h to obtain SnO 1.8 F 0.4 Conductive oxide.
[0067] Step 3:
[0068] The layered oxide (calculated based on the molar amount of transition metal therein) obtained in step 1 and the conductive oxide are mixed in a molar ratio of 98:2, the mixer speed is 1500 rpm, and the mixing time is 10 min. After the mixing is completed, the mixture is sintered at 700 ° C for 8 h in an air box furnace with a positive pressure of 60 Pa to obtain a conductive oxide-coated modified layered oxide positive electrode material.
[0069] Embodiment 2:
[0070] Compared with Example 1, the only difference is that the layered oxide positive electrode material prepared in step 1 is changed. The different step 1 is: mixing transition metal oxides and Na2CO3 according to a sodium / transition metal molar ratio of 1.03; the transition metal oxides include NiO, Fe2O3 and MnO2 with a Ni:Fe:Mn molar ratio of 0.33:0.33:0.34. The configured oxide precursor and Na2CO3 are added to the high-speed mixer in sequence, the mixing speed is 2000rpm, the mixing time is 10min, the mixing is uniform without white spots, the mixture is pre-sintered at 500℃ for 8h in an air box furnace, then heated to 1300℃ and calcined for 11h, cooled to room temperature with the furnace, and the layered oxide is obtained after roller crushing and air flow pulverization.
[0071] Other operations and parameters are the same as in Example 1.
[0072] Example 3: Case of changing the type of modifier
[0073] Compared with Example 1, the only difference is that the modifier is changed. The experimental groups are:
[0074] Group A: the modifier is SnO2; other operations and parameters are the same as those in Example 1;
[0075] Group B: the modifier is In2O3; other operations and parameters are the same as those in Example 1;
[0076] Group C: Modifier is ZnO 0.8 F 0.4
[0077] The preparation steps of the modifier are as follows: adding ZnO and NH4F powders with a F:Zn molar ratio of 4:10 into a vertical mixer and mixing them evenly, the mixer speed is 2000 rpm, the mixing time is 10 minutes, and then the mixture is sintered at 850° C. for 14 hours to obtain F-doped ZnO conductive oxide; other operations and parameters are the same as those in Example 1;
[0078] Group D: Modifier is In2SnO5
[0079] In2O3 and SnO2 powders with a molar mass ratio of In to Sn of 2:1 were added to a vertical mixer and mixed evenly. The mixer speed was 2000 rpm and the mixing time was 10 min. The mixture was then sintered at 950° C. for 11 h to obtain In2SnO5 conductive oxide. Other operations and parameters were the same as those in Example 1.
[0080] Group E: Modifier is In2SnO 4.8 F 0.4
[0081] In2O3, SnO2 and NH4F powders with a molar mass ratio of In, Sn and F of 20:10:4 were added into a vertical mixer and mixed evenly. The mixer speed was 2000 rpm and the mixing time was 10 min. Then the mixture was sintered at 900 °C for 12 h to obtain In2SnO 4.8 F 0.4 Conductive oxide; other operations and parameters are the same as in Example 1.
[0082] Example 4: Changing the amount of modifier
[0083] Compared with Example 1, the only difference is that in step 3, the molar ratio of the modifier to the transition metal element in the layered oxide prepared in step 1 is 4:96; other operations and parameters are the same as in Example 1.
[0084] Embodiment 5:
[0085] Compared with Example 1, the only difference is that the sintering conditions in step 3 are changed. The experimental groups are:
[0086] Group A: sintering temperature is 800°C, time is 6h; other operations and parameters are the same as those in Example 1;
[0087] Group B: The sintering pressure was positive 20 Pa; other operations and parameters were the same as those in Example 1.
[0088] Comparative Example 1
[0089] Compared with Example 1, the only difference is that steps 2 and 3 are not performed, and the layered oxide prepared in step 1 is directly used as the active material. Other operations and parameters are the same as those in Example 1.
[0090] Comparative Example 2
[0091] Compared with Example 1, the only difference is that ZnO is used as the modifier, and its dosage and other operations and parameters are the same as those in Example 1.
[0092] Comparative Example 3
[0093] Compared with Example 1, the only difference is that the modifier is prepared in advance in step 2, and the initiator is mixed with the raw materials of step 1, and both are calcined under the conditions of step 1, and then sintered in step 3 to obtain a composite material.
[0094] Comparative Example 4
[0095] Compared with Example 1, the only difference is that in step 3, no sintering treatment is performed, and other operations and parameters are the same as in Example 1.
[0096] Comparative Example 5
[0097] Compared with Example 1, the only difference is that in step 3, the sintering furnace is not set to positive pressure, and other operations and parameters are the same as in Example 1.
[0098] Test Case
[0099] The conductive oxide-coated layered oxide in the embodiment and the comparative example was used as the positive electrode material to assemble a half-cell, the modified positive electrode material and the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) were dispersed in a nitrogen methyl pyrrolidone (NMP) solvent at a mass ratio of 8:1:1, stirred evenly, and an electrode slurry was obtained. The electrode slurry was coated on the surface of aluminum foil, vacuum-baked at 80°C for 12 hours, rolled, and cut to obtain a positive electrode sheet; with a sodium sheet negative electrode, 1 mol / L NaPF6 and a two-component mixed solvent of EC:DMC=1:1 (v / v) were used to form an electrolyte, and a polypropylene microporous membrane was used as a diaphragm to assemble a CR2032 button cell in an argon-filled glove box. The following tests were performed:
[0100] Rate: Constant current charge and discharge test at 2~4.2V / 0.1 / 10C at 25℃.
[0101] Low temperature performance: Constant current charge and discharge tests were performed at -20℃ and 25℃ at 2~4.2V / 0.1C.
[0102] Cycle: Perform constant current charge and discharge cycle test at 25℃, 2~4.2V / 1C for 200 cycles.
[0103] The results are shown in Table 1.
[0104] Table 1
[0105]
[0106]
[0107] from Figures 1 to 4From the SEM images, it can be seen that Example 1 has a uniform and dense coating layer on the particle surface compared with Comparative Example 1 which has not been treated in Steps 2 and 3; Comparative Example 4 which has not been subjected to the heat treatment process in Step 3 has only granular conductive oxide on the surface, and there is no coating effect; while for Comparative Example 5 which has not been subjected to positive pressure heat treatment, the surface layer of the material is uneven island-shaped coating. This indicates that the heat treatment in Step 3 can regulate the surface structure so that the conductive oxide is in-situ coated on the surface of the base material, with a higher degree of adhesion, and the positive pressure setting can make the coating layer more uniform and dense.
[0108] It can be seen from the examples and comparative examples that the special modifier described in the present invention can be used to optimize the coating of the layered oxide positive electrode material with the conductive oxide and the gradient doping modification process based on the positive pressure sintering process from outside to inside, thereby improving the volume strain and interface problems of the layered oxide positive electrode material under high charging cut-off voltage while maintaining the original rate performance of the material;
[0109] In addition, it can be seen from Examples 1 and 2 that the selection of multi-doped bulk materials can obtain better rate and low temperature performance. It can be seen from Examples 1 and 3 that the selection of cationic and / or anionic hybrid modifiers, combined with the outside-to-inside sintering coating and exosmotic gradient doping, can obtain better fast charging and low temperature performance.
[0110] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0111] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a modified positive electrode active material for a sodium ion battery, characterized in that: Will Na X TMO2 layered oxide and modifier are mixed and then calcined under positive pressure to obtain; Na X In the TMO2 layered oxide, the TM is one or more of Ni, Fe, Mn, Cu, Ca, Mg, Ti, Al, Zn, Zr, Sn, Sb, and W; the x is 0.5 to 1; The modifier described above is M a N b O c Y d ; M is at least one of Sn, In, and Cd; N is at least one of Ga, Sb, Ba, Al, Ti, Zr, La, Ce, Mo, W, Au, Sr, Hf, and Ta; Y is at least one of F, Cl, Br, and I; 0 < a ≤ 1; b is 0 to 0.5; d is 0 to 0.5; c is 2 to 0.5d.
2. The method for preparing a modified positive electrode active material for a sodium ion battery according to claim 1, characterized in that: The Na X TMO2 layered oxide is obtained by sintering Na source and TM source; Preferably, the Na source comprises at least one of sodium carbonate, sodium sulfate, sodium nitrate, sodium phosphate, sodium chloride and sodium fluoride; Preferably, the TM source is at least one of carbonate, hydroxide, organic acid salt and oxide of TM element; Preferably, the TM comprises at least one of Ni, Fe, and Mn, and selectively comprises one or more of Cu, Ca, Mg, Ti, Al, Zn, Zr, Sn, Sb, and W; Preferably, the molar ratio of Na / TM in the Na source and the TM source is 0.5-1.07; Preferably, the sintering temperature is 800-1500°C; Preferably, the sintering time is 10 to 15 hours.
3. The method for preparing a modified positive electrode active material for a sodium ion battery according to claim 1, characterized in that: The modifier is SnO2, In2O3, CdO, SnO 2-0.5d F d 、InO 2-0.5d F d , CdO 2-0.5d Br d Sn a Sb b O2、In a Sn b O2、In a Cd b O2、Sn a Sr b O2、In a Ga b O2、Sn a La b Ba c O2、Sn a Ce b O2、In a Ce b O2、In a Sn b O 2-0.5d F d Sn a Sb b O 2-0.5d F d At least one of; Preferably, the M a N b O c Y d In the modifier, b and c are not 0 at the same time; Preferably, the M a N b O c Y d The method is obtained by mixing and calcining source materials containing the elements; wherein the calcination temperature is 800 to 1500° C.; and the calcination time is preferably 10 to 15 hours.
4. The method for preparing a modified positive electrode active material for a sodium ion battery according to claim 1, characterized in that: Based on the molar mass of transition metal, the modifier is Na X 1-5 mol% of TMO2 layered oxide and modifier mixture.
5. The method for preparing a modified positive electrode active material for a sodium ion battery according to claim 1, characterized in that: The calcination temperature is 500-900°C, and the time is preferably 2-10h; Preferably, the atmosphere during the calcination stage is an oxygen-containing atmosphere; Preferably, the pressure in the calcination stage is +20 to +100 Pa.
6. A modified positive electrode active material obtained by the preparation method according to any one of claims 1 to 5.
7. Use of a modified positive electrode active material obtained by the preparation method according to any one of claims 1 to 5, characterized in that: It is used as positive electrode active material to prepare sodium ion batteries.
8. A positive electrode material for a sodium ion battery, characterized in that: The modified positive electrode active material comprises the modified positive electrode active material prepared by the preparation method according to any one of claims 1 to 5.
9. A positive electrode of a sodium ion battery, characterized in that: Contains the positive electrode material according to claim 8.
10. A sodium ion battery, characterized in that: The positive electrode according to claim 9 is included.
Citation Information
Patent Citations
Layered positive electrode material of sodium-ion battery and preparation of layered positive electrode material
CN113644268A
Modified sodium ion battery positive electrode material and preparation method and application thereof
CN116130620A
Preparation method of layered oxide positive electrode material, material and application thereof
CN117594769A
Sodium ion positive electrode material, preparation method thereof and sodium ion battery
CN118039868A
P2 type sodium ion positive electrode material and preparation method thereof
CN119133431A